Study Atas Putusan No 254/PID.B/2017/PN LLG Kepemilikan Senjata Tajam di Pengadilan Negeri Lubuk Linggau - Apriansyah, Apriansyah; Romli, Romli; Yusuf, Hambali (Universitas Semarang, 2025)
This research was conducted at the Lubuk Linggau District Court, South Sumatra. This study aims to examine and analyze the legal rules on criminal acts without the right to carry sharp weapons in the Musi Rawas Lubuk Linggau area. The method used in this study is a normative legal research method that is descriptive analysis, namely research conducted by examining library materials (secondary data) or library legal research. The types and sources of data used in this study are Types of data, Data sources and, data collection techniques used in this study using library research. Based on the research results, in terms of ownership of sharp weapons, anyone without exception can be punished in this case, and when is a person declared as a perpetrator of the crime of ownership of sharp weapons as written in the rules as regulated and threatened with criminal penalties in Article 2 paragraph (1) of Law/drt/No.12 of 1951. Like the case study discussed in this case, the case of